The slave dancer : a novel - Fox, Paula; Keith, Eros (Scarsdale, N.Y. : Bradbury Press, 1973)
Kidnapped by the crew of an Africa-bound ship, a thirteen- year-old boy discovers to his horror that he is on a slaver and his job is to play music for the exercise periods of the human cargo.
970
Newbery Medal, 1974
Keywords: Slave trade -- Fiction